The EFL Learner’s Perspectives About Accuracy, Fluency, and Complexity in Daily Routines - Ikrar Genidal Riadil (Faculty of Education and Teachers Training, 2019)
AbstractThe significant care and the globalization of English have been caused broad demand for good English-speaking skills in various realms. The aim of this research is getting to know what people think accuracy, fluency and complexity when they are speaking or writing in English. Many students think too much of grammatical-error and they need to remember all tenses so they can practice English. Students need motivation from their-selves before they learn English; moreover, English as foreign language, students will study English as they must pass their subject in school. In addition, the present paper aimed to know the people perception of accuracy, fluency and complexity in written and spoken English. The researchers use qualitative research method and open questions for questionnaire. The study data is collected from 10 students of English Education department in Tidar University. Therefore, 50% students chose fluency, 30% students chose accuracy, and 20% chose complexity. The result of this research, students chose fluency because by mastering fluency in speaking, students can correct them in grammatical structure by the time. As one respondent said that fluent in English is basic and it is better if we fluent then accurate by correcting their grammatical structure. In the end, the researchers knew that students prefer fluent then accurate so they can complex in English. Keywords: Learning English, accuracy, fluency, complexity